An evaluation of depression, anxiety and fatigue in patients with Behçet's disease. (5th November 2018) - Can Sandikci, Sevinc; Colak, Seda; Omma, Ahmet; Enecik, Mehmet E.
Abstract: Objectives: Behçet's disease (BD) is a type of systemic vasculitis and inflammatory disease of unknown etiology, which is associated with fatigue and lower quality of life (QoL). The aim of this study was to assess the relationship between Behçet's Disease Current Activity Form (BDCAF) and Behçet's Disease Quality of Life (BDQoL), depression, anxiety and fatigue in Behçet's disease. Methods: We conducted a cross‐sectional study of 155 BD patients and 107 healthy subjects in a single center over a 1 year period. All participants completed the Multidimensional Assessment of Fatigue (MAF) questionnaire, and the Hospital Anxiety and Depression (HADS) scale. Disease activity in the BD patients was assessed using the BDCAF, and the physician's global assessment (PGA). BD patients also completed the BDQoL questionnaire. Results: There was no significant difference in age and gender between the groups. BD patients had significantly higher HADS‐anxiety (HADS‐A), HADS‐depression (HADS‐D) and MAF scores than the healthy control group ( P < 0.05). BD patients with active disease had significantly higher MAF and HADS‐A scores compared to inactive BD patients ( P < 0.05). MAF scores showed positive correlations with HADS‐A, HADS‐D, BDCAF and BDQoL. Conclusions: Fatigue and anxiety are common in clinically active BD patients compared with healthy control subjects and inactive BD patients.